The Multispecies Salon. - Kirksey, Eben (Duke University Press, 2014)
A new approach to writing culture has arrived: multispecies ethnography. Plants, animals, fungi, and microbes appear alongside humans in this singular book about natural and cultural history. Anthropologists have collaborated with artists and biological scientists to illuminate how diverse organisms are entangled in political, economic, and cultural systems. Contributions from influential writers and scholars, such as Dorion Sagan, Karen Barad, Donna Haraway, and Anna Lowenhaupt Tsing, are featured along with essays by emergent artists and cultural anthropologists.